Responses of the reproduction, population growth and metabolome of the marine rotifer Brachionus plicatilis to tributyl phosphate (TnBP). (15th March 2021) - Zhang, Xin; Tang, Xuexi; Yang, Yingying; Sun, Zijie; Ma, Wenqian; Tong, Xin; Wang, Chengmin; Zhang, Xinxin
Abstract: The typical alkyl organophosphorus flame retardant tributyl phosphate (TnBP) can leak from common products into the marine environment, with potential negative effects on marine organisms. However, risk assessments for TnBP regarding zooplankton are lacking. In this study, a marine rotifer, Brachionus plicatilis, was used to analyze the effect of TnBP (0.1 μg/L, environmental concentration; 1 and 6 mg/L) on reproduction, population growth, oxidative stress, mitochondrial function and metabolomics. Mortality increased as the TnBP concentration rose; the 24-h LC50 value was 12.45 mg/L. All tested TnBP concentrations inhibited B. plicatilis population growth, with reproductive toxicity at the higher levels. Microstructural imaging showed ovary injury, the direct cause of reproductive toxicity. Despite elevated glutathione reductase activities, levels of reactive oxygen species and malonyldialdehyde increased under TnBP stress, indicating oxidative imbalance. TnBP induced mitochondrial malformation and activity suppression; the ROS scavenger N-acetylcysteine alleviated this inhibition, suggesting an internal connection. Nontargeted metabolomics revealed 398 and 583 differentially expressed metabolites in the 0.1 μg/L and 6 mg/L treatments relative to control, respectively, which were enriched in the pathways such as biosynthesis of amino acids, purine metabolism, aminoacyl-tRNA biosynthesis. According to metabolic pathway analysis, oxidative stress from purine degradation, mitochondrial dysfunction, disturbed lipid metabolism and elevated protein synthesis were jointly responsible for reproduction and population growth changes. This study echoes the results previously found in rotifer on trade-off among different life processes in response to environmental stress. Our systematic study uncovers the TnBP toxic mode of action. Graphical abstract: Image 1 Highlights: TnBP with environmental concentration can retard the population growth of rotifer. Mitochondria in rotifers were the subcellular targets of TnBP. TnBP promoted the degradation of purine, accompanied by ROS overproduction. Lipid metabolism of rotifer varied with TnBP concentrations. Rotifer counteracted/resisted metabolic imbalance by sacrificing the reproduction and population growth. Abstract : Metabolic disturbances, oxidative stress and mitochondrial dysfunction worked together to alter the reproduction and population growth of rotifer under TnBP stress.